Quantifying the Effect of Plasmaspheric Hiss on the Electron Loss From the Slot Region. Issue 5 (22nd May 2020) - Kim, Kyung‐Chan; Shprits, Yuri; Wang, Dedong
Abstract: We present global statistical models of both wave amplitude and wave normal angle (WNA) of plasmaspheric hiss using Van Allen Probe‐A observations. They utilize the time history of solar wind parameters, that is, interplanetary magnetic field B Z and solar wind speed, and the AE index for each measurement of hiss waves as inputs. The solar wind parameter‐based model generally results in higher performance than using only the AE index as an input. Both observations and model results reveal a clear dependence of hiss wave distribution on the magnetic local time (MLT): Higher amplitudes with field‐aligned (<30 o ) WNAs occur more frequently on the dayside than on the nightside. Such a tendency does not depend on magnetic latitude (MLAT), but slightly larger WNAs with a relatively low amplitude frequently appear for larger MLAT (>10 o ). We also examine how significantly the electron loss rates in the slot region can be changed by incorporating the model output of hiss waves into a diffusive transport simulation. Simulation results show that during a typical timescale (roughly a couple of days) of a corotating interaction region‐driven storm, the nightside hiss waves with larger WNA (>30 o ) do not contribute to the electron loss in the slot region due to their low amplitude and large WNA, while dayside hiss with WNAs less than 30 o and comparatively higher amplitudes leads to a fast drop in flux, especially for electrons of a few hundred keV. Key Points: We develop statistical models of both wave amplitude and wave normal angle of plasmaspheric hiss Model calculation results show a clear day‐night asymmetry of the wave distribution Dayside hiss predominantly contributes to electron loss in the slot region compared to nightside hiss